How have English councils' funding and spending changed? 2010 to 2024 - Kate Ogden; David Phillips (Institute for Fiscal Studies (IFS), 2024)
Like spending on the NHS, and schools, English council funding has increased over the current parliament. But that follows a decade of austerity in the 2010s. And despite funding increases, councils are again under significant financial pressure, with increases in spending outpacing revenues and reserves being drawn down. Some, very publicly, have had to take emergency measures to bolster their budget - most notably Birmingham City Council, Europe's largest lower-tier council. And more generally, spending continues to be increasingly concentrated on services for a relatively small number of residents with the most acute needs. In this context, this report looks at how council funding and spending are set to have changed over the current (2019-24) parliament and puts these changes in a longer-run context back to 2010. What emerges is a picture of two interconnected challenges on the level and distribution of funding that the next government will need to grapple with - and which the worrying outlook for the overall public finances will make especially difficult to address.
Keywords: 330; Government finances and spending; Distributional effects; Public sector; Government spending; Local government finance; Trends